Exploring acute care nurses' decision‐making in psychotropic PRN use in hospitalised people with dementia. Issue 13 (18th September 2020) - Walsh, Brittany; Dahlke, Sherry; O'Rourke, Hannah; Hunter, Kathleen F.
Abstract: Aims and objectives: To understand how acute care nurses make decisions about administering "as‐needed" (PRN) psychotropic medications to hospitalised people with dementia (PWD). Background: Behavioural and psychological symptoms of dementia occur in approximately 75% of PWD admitted to acute care. Despite this, few studies provide insight into the use and prevalence of psychotropic use in acute care. Design: A qualitative descriptive design was used to explore acute care nurses' decision‐making about PRN psychotropic medication administration to PWD. Methods: Semi‐structured interviews were conducted with eight nurses from three acute care medical units in a large tertiary hospital in Western Canada. Conventional content analysis was used to develop three themes that reflect nurses' decision‐making related to administering PRNs to hospitalised PWD. COREQ guidelines were followed. Results: Three themes of legitimising control, making the patient fit and future telling were developed. Legitimising control involved medicating undesirable behaviours to promote the nurses' perceptions of safety. Making the patient fit involved maintaining routine and order. Future telling involved pre‐emptively medicating to prevent undesirable behaviours from escalating. Nurses provided little to no mention of assessing for physical causes contributing to behaviours. PRNs were seen as a reasonable alternative to physical restraints and were frequently used. Additionally, organisational and unit routines greatly influenced nurses' decision‐making. Conclusions: These findings provide an initial understanding of how nurses make decisions to administer PRN medications to hospitalised older people and may inform prescribing practices. There were novel findings about the lack of assessment prior to PRN administration, and the nurses' collective response in decision‐making. More research is needed to better understand the complexities of nurses' decision‐making, to assist in the development of interventions for nursing practice.